Karol Wojtyła senior w wojsku austriackim i polskim - Kindziuk, Milena (Saeculum Christianum. Pismo Historyczne, 2018)
Little is known and studied of the Military personal records of Karol Wojtyla, from Vienna Kriegsarchiv until now which in turn has allowed for the accurate reproduction of his curriculum vitae, as well as taking into account the main steps in the course of his military service. Their analysis leads to the conclusion that Karol Wojtyla, senior, John Paul II’s father was a professional soldier for 18 years in service in the Austro-Hungarian Army, in the 56th Infantry Regiment called Regiment of Wadowice, and later became an officer in the Polish Army in the reborn Polish Republic. Throughout the period of his military service he enjoyed a very good reputation: Superiors characterized him as a diligent and honest, valued for his ability to communicate in German.